A study of essential oil from an invasive Piper aduncum L. - I Putu Agus Hendra Wibawa; Vienna Saraswaty; Farid Kuswantoro; Putri Sri Andila; Putri Kesuma Wardhani; I Gede Tirta; Wawan Sujarwo (Jurnal Biologi Udayana, 2019)
An invasive Piper aduncum is a plant species that potentially produces essential oil. The study aims todetermine the percentage, phytochemical compounds, and anti-fungal properties of essential oil producedfrom the leaves and fruits of Piper aduncum. The study showed that the leaves and fruits of P. aduncumcontain 0.30% and 0.33% of essential oil, respectively. Apiol is the most abundant phytochemical compoundobtained in essential oil of leaves and fruits of P. aduncum with 57.10% and 66.31%, respectively. Weconclude that essential oil obtained in this study is able to inhibit the growth of both Aspergillus niger andCladosporium sp. but not for Fusarium oxysporum and Fusarium solani.